Letter: CYP3A4/5 genotype status and outcome of vonoprazan‐containing Helicobacter pylori eradication therapy in Japan. Issue 7 (3rd March 2017) - Sugimoto, M.; Ban, H.; Hira, D.; Kamiya, T.; Otsuka, T.; Inatomi, O.; Bamba, S.; Terada, T.; Andoh, A.
Abstract : Linked Content This article is linked to Sakurai et al and Mori and Okamoto papers. To view this article visithttps://doi.org/10.1111/apt.13325 .